Effect of whole-crop barley and oat silages on the performance of mature suckler cows and their progeny in outdoor winter feeding - Manninen, Merja; Virkajärvi, Perttu; Jauhiainen, Lauri (Elsevier, 2005)
This study was undertaken to assess during the winter feeding period the effects of replacing grass silage (G) with whole-crop barley silage (B) or whole-crop oat silage (O) on suckler cow and calf performance. Forty-eight Hereford cows with an initial live weight of 741 kg (S.D. 78.5) were selected for the experiment. The diet was either G, B or O as a sole feed. The aim was to offer the cows the same amount of energy in all diets. Therefore, the energy content of the silages was evaluated prior to the experiment by measuring the in vitro organic matter digestibility which resulted in 11.7 MJ metabolizable energy (ME)/kg dry matter (DM) for G and 9.9 MJ ME/kg DM for B and O. During the experiment, the digestibility of the silages was measured by both in vitro and in vivo methods. The ME values of G, B and O evaluated by the in vivo method were 11.2, 10.5 and 9.5 MJ/kg DM, respectively. The DM intake on diets G, B and O averaged 9.2, 10.5 and 10.3 kg which resulted in ME intakes of 102, 109 and 97 MJ ME/d, respectively. The type of roughage affected the in vivo apparent protein digestibility co-efficients which for G, B and O were 0.841, 0.698 and 0.498, respectively (G versus B, P < 0.05; G versus O and B versus O, P < 0.01). The initial cow body condition score (BCS) averaged 3.2 (S.D. 0.23). Pre-grazing the change of BCS and the live weight gain (LWG) for G, B and O cows was on average 0.23, 0.09 and -0.39 (G versus O and B versus O, P < 0.001) and -20, -9 and -56 kg (G versus O, P < 0.05; B versus O, P < 0.01), respectively. All calves were born before the grazing season and milk and grass were the sole feeds at pasture. The pre-weaning calf LWG was not affected by the diets averaging 1357 g/d. The daily milk yield on diets G, B and O averaged 11.4, 10.3 and 9.5 kg (G versus O, P < 0.05), respectively. Forty-two out of 48 cows entered the mating period of which all were observed to be pregnant. The interval from calving to conception averaged 89 days. B and O proved to be suitable winter feeds for mature suckler cows in cold winter circumstances. Especially O had a lower energy and protein content than G but fulfilled the energy and protein demands of mature, pregnant beef cows in good body condition.
Keywords: Ko; ruokinta; emolehmät; maito; kokoviljasäilörehu; laiduntaminen; feeding beef; reproduction; grazing; milk; body condition; whole-crop cereal silage